Tailoring biomineralization and biodegradation of Mg–Ca alloy by acetic acid pickling - Shebeer A Rahim; M A Joseph; Hanas T (Materials Research Express, 2020)
Magnesium and its alloys are suitable candidates for developing biodegradable metallic implants. However, the rapid degradation of these alloys in the physiological environment is a major limitation for such applications. In this work, Mg–Ca alloy was chemically treated with acetic acid and its effects on degradation behaviour were studied using simulated body fluid (SBF). The surface morphology and composition of the acid pickled samples were investigated using a scanning electron microscope (SEM) and infrared spectroscopy (IR). The degradation rate was analysed by conducting potentiodynamic polarization (PDP) and immersion tests. The results show that optimum acetic acid treatment improved the corrosion resistance by acid etching and formation of magnesium acetate layer. The treated samples also exhibited enhanced biomineralization and developed calcium phosphate layer on the surfaces during immersion tests. It is proposed that acetic acid pickling can be used as a reliable technique for surface modification as well as for pre-treatment of magnesium alloys to make them suitable for degradable metallic implant applications.